Artificial Intelligence and Evolutionary Computations in Engineering Systems Proceedings of ICAIECES 2017 - Dash, Subhransu Sekhar; Naidu, Paruchuri Chandra Babu.; Bayindir, Ramazan; Das, Swagatam; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book is a collection of high-quality peer-reviewed research papers presented in the International Conference on Artificial Intelligence and Evolutionary Computations in Engineering Systems (ICAIECES 2017). The book discusses wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academia and industry have presented their original work and ideas, information, techniques and applications in the field of communication, computing and power technologies.
Preface -- About the Editors -- Table of Contents -- 72 papers -- Author Index.
Keywords: Computational intelligence; Artificial intelligence; Algorithms; Computational Intelligence; Artificial Intelligence; Algorithms